The Linear ubiquitin chain assembly complex acts as a liver tumor suppressor and inhibits hepatocyte apoptosis and hepatitis. Issue 6 (10th April 2017) - Shimizu, Yutaka; Peltzer, Nieves; Sevko, Alexandra; Lafont, Elodie; Sarr, Aida; Draberova, Helena; Walczak, Henning
Abstract : Linear ubiquitination is a key posttranslational modification that regulates immune signaling and cell death pathways, notably tumor necrosis factor receptor 1 (TNFR1) signaling. The only known enzyme complex capable of forming linear ubiquitin chains under native conditions to date is the linear ubiquitin chain assembly complex, of which the catalytic core component is heme‐oxidized iron regulatory protein 2 ubiquitin ligase‐1–interacting protein (HOIP). To understand the underlying mechanisms of maintenance of liver homeostasis and the role of linear ubiquitination specifically in liver parenchymal cells, we investigated the physiological role of HOIP in the liver parenchyma. To do so, we created mice harboring liver parenchymal cell–specific deletion of HOIP ( Hoip Δhep mice) by crossing Hoip ‐floxed mice with albumin–Cre mice. HOIP deficiency in liver parenchymal cells triggered tumorigenesis at 18 months of age preceded by spontaneous hepatocyte apoptosis and liver inflammation within the first month of life. In line with the emergence of inflammation, Hoip Δhep mice displayed enhanced liver regeneration and DNA damage. In addition, consistent with increased apoptosis, HOIP‐deficient hepatocytes showed enhanced caspase activation and endogenous formation of a death‐inducing signaling complex which activated caspase‐8. Unexpectedly, exacerbated caspase activation and apoptosis were not dependent on TNFR1, whereas ensuing liver inflammation and tumorigenesis were promoted by TNFR1 signaling. Conclusion : The linear ubiquitin chain assembly complex serves as a previously undescribed tumor suppressor in the liver, restraining TNFR1‐independent apoptosis in hepatocytes which, in its absence, is causative of TNFR1‐mediated inflammation, resulting in hepatocarcinogenesis. (Hepatology 2017;65:1963‐1978).